Evaluating the relationship between ductal carcinoma in situ, calcifications, and margin status in patients undergoing breast conserving surgery. Issue 6 (11th February 2019) - Bruenderman, Elizabeth H.; Bhutiani, Neal; Mercer, Megan K.; McMasters, Kelly M.; Sanders, Mary Ann G.; Ajkay, Nico lás
Abstract: Background: Microcalcifications associated with ductal carcinoma in situ (DCIS‐AMC) close to lumpectomy margins could be used as a surrogate for margin involvement and aid in decreasing margin re‐excision. We sought to evaluate the histologic factors of DCIS‐AMC near lumpectomy margins. Methods: Women with DCIS treated with breast‐conserving surgery (BCS) who had DCIS‐AMC on surgical specimens were identified. Pathology slides were reviewed to determine the distance of DCIS‐AMC from each margin (six per specimen) and the distance of DCIS from each margin (ie, margin status). Results: Of 35 patients (210 margins), 24 had close/positive margins (39 margins [18%]). DCIS‐AMC≤10 mm from a margin was associated with a greater incidence of DCIS≤2 mm from the margin (31.7% DCIS‐AMC≤10 mm vs 13.3% no DCIS‐AMC≤10 mm, P  = 0.003). On multivariable analysis, DCIS≤2 mm from the margin was independently associated with DCIS‐AMC≤10 mm from the margin (odds ratio 2.95, 95% confidence interval 1.48‐5.86, P  = 0.002). Conclusions: DCIS‐AMC≤10 mm from the inked margin is associated with DCIS at or close to the margin (≤2 mm). Using this knowledge, intraoperative techniques like specimen radiography could be utilized to detect microcalcifications≤10 mm from a margin and guide selective margin re‐excision in BCS.